MANAJEMEN PEMASARAN DAN SISTEM INFORMASI PENDIDIKAN - Viviana, Viviana; Shabirah, Raafanisa; Putri, Tsabita Ananda; Maftuhah, Maftuhah; Taufiqurrahman, Taufiqurrahman (STKIP Pesisir Selatan, 2025)
This article aims to comprehensively analyze and elaborate on the crucial role of marketing management and educational information systems (IS) in improving the quality and operational efficiency of educational institutions in the digital era. The primary objective is to present a conceptual framework that integrates these two disciplines to achieve more effective and sustainable educational goals. This study uses a descriptive qualitative approach through library research. Data were collected from various academic literature sources discussing marketing management, information systems, and educational management. Data analysis techniques were conducted descriptively by synthesizing and interpreting information to build arguments and conclusions. The results of the study indicate that the synergy between educational marketing management and IS is fundamental. Strategic marketing management requires accurate data from IS to identify market needs, develop relevant programs, and communicate effectively with stakeholders. Conversely, IS provides the technological infrastructure to manage student, staff, curriculum, and financial data, all of which support marketing decisions. This integration enables educational institutions to respond to market dynamics, increase accountability, and achieve competitive advantage through optimal use of data and technology.